Enhancing antimicrobial efficacy: Gum acacia-enriched Lactobacillus consortium against multidrug-resistant pathogens - Jinal Bhola; Rama Bhadekar (Medicine in Microecology)
The escalating challenge of antimicrobial resistance (AMR) has rendered many pathogens impervious to conventional antibiotics, necessitating novel therapeutic approaches. This study evaluates the antimicrobial potential of a Gum Acacia-enriched Active GRAS Consortium (AGC), composed of Lactobacillus plantarum, L. acidophilus, and L. casei var. rhamnosus, against multidrug-resistant (MDR) pathogens. AGC formulations, with (Set IV) and without (Set III) gum acacia, were tested against clinical isolates of Staphylococcus aureus, Acinetobacter baumannii, Klebsiella pneumoniae, and Escherichia coli. Set IV demonstrated significantly enhanced antimicrobial activity, with inhibition zones reaching 18.7 mm, minimum inhibitory concentrations (MIC) as low as 0.83 mg/ml, and strong biofilm inhibition. Mechanistic assays revealed amplified DNA release from treated pathogens and unique antimicrobial protein profiles (<6.5 kDa) stabilized by gum acacia. Scanning electron microscopy confirmed severe ultrastructural damage, including membrane disruption and lysis, in Set IV-treated pathogens. Adhesion assays on Caco-2 cells highlighted Set IV's ability to reduce pathogen adhesion to 5 %, outperforming non-GA enriched formulation. These results underscore the synergistic role of probiotics and natural polysaccharides, like gum acacia, in combating MDR pathogens. Set IV's dual action-direct pathogen inhibition and biofilm disruption-positions it as a promising candidate for alternative or adjunctive therapies in AMR management. This study highlights the potential of integrating probiotics and prebiotics to create innovative solutions addressing the global AMR crisis.